Continental‐scale water‐level response to a large earthquake. Issue 1 (19th September 2014) - Shi, Z.; Wang, G.; Manga, M.; Wang, C.‐Y.
Abstract: Co‐seismic groundwater‐level changes induced by earthquakes have been reported for thousands of years. The M8.0 Wenchuan earthquake caused co‐seismic groundwater‐level responses across the Chinese mainland. Three types of changes were recorded in 197 monitoring wells: co‐seismic oscillations ranging in amplitude from 0.004 to 1.1 m, immediate co‐seismic step changes ranging from 0.0039 to 9.188 m, and more gradual postseismic changes ranging from 0.014 to 1.087 m. We find that the co‐seismic groundwater‐level response is complex. There is neither a clear relationship between the response amplitude and the distance from the epicenter, nor a clear relationship between the groundwater response and lithology at the continental scale. Both the sign and amplitude of water‐level changes are random at the continental scale, and a poroelastic response to the co‐seismic static strain cannot explain most of the co‐seismic changes. However, wells located near the edges of tectonically active blocks have larger response amplitudes than those in the middle of these 'stable' blocks. Considered together, these observations indicate that permeability enhancement caused by the earthquake is a significant or dominant mechanism causing water‐level changes. These data indicate that large earthquakes can cause the widespread permeability changes in the shallow crust although the magnitude of permeability change is uncertain. Abstract : We report the co‐seismic groundwater level response to the M8.0 earthquake across the Chinese mainland. There is great variability in the relationship between water level changes, and epicentral distance or static strain. Permeability enhancement in the crust caused by the earthquake is a significant or dominant mechanism in causing water level changes.